Peran Budaya Organisasi dalam Mengoptimalkan Kinerja Pegawai pada Kelurahan Lebak Bulus Jakarta Selatan - Azira Zahra Hasibuan; Pusporini Palupi Jamaludin; Paringsih Paringsih (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to analyze the role of organizational culture in optimizing employee performance in Lebak Bulus Village, South Jakarta. A strong organizational culture is considered to have a significant contribution in improving the effectiveness of government officials and the quality of public services to the community. This study uses a qualitative descriptive approach with a phenomenological method, which emphasizes an in-depth understanding of the experiences, views, and behaviors of employees in carrying out their duties in their work environment. The research focuses on actors (employees), social situations, and activities that occur within the village environment. Data collection techniques were carried out through observation, in-depth interviews with key and primary informants, and documentation. Data validity was tested through triangulation of sources and techniques to increase the validity of the research results. The results show that the organizational culture in Lebak Bulus Village has strengths in the aspects of innovation and risk-taking, orientation towards results, orientation towards people, and stability. However, several weaknesses were still found, such as low individual initiative, lack of attention to detail, weak team orientation, minimal levels of aggressiveness, and limited employee experience and accuracy. Opportunities for improvement can be pursued through ongoing training and the digitalization of public services, although challenges remain, including a passive work culture and resistance to policy change. Overall, organizational culture plays a crucial role in supporting employee performance improvement, but a sustainable strategy is needed to strengthen professionalism and build a more adaptive and progressive work culture. Efforts to address identified weaknesses, such as improving communication between employees, developing leadership skills, and enhancing discipline in carrying out tasks, are essential for the continued development of a positive organizational culture. Furthermore, awareness of the importance of collaboration across organizational divisions must be instilled to create a more productive and efficient work environment.